Effectiveness of Guided Inquiry Learning Model and Problem Based Learning Learning Model on Thematic Integrated Learning Competency - Reny Novita Sari; Yuni Ahda; Yanti Fitria (Postgraduate School, Universitas Negeri Padang, 2019)
Learning competencies of 5th grade elementary school students in integrated thematic learning are still relatively low. This happens because the use of learning models still does not match the material and character of students. One effort that can be done to overcome this problem is by implementing a guided inquiry model and the Problem Based Learning model in the learning process. This type of research is a quasi experiment with a preetest-posttest only control group design. Data were analyzed using t test. From the results of the analysis obtained: (1) there is effectiveness in the use of Guided Inquiry models to improve learning competency aspects of knowledge, because tcount is 20.5649> table 1.7011 (2) there is effectiveness in using Problem Based Learning learning models to improve tcounting learning competency of 8.5467> ttable 1.6991 (3) there is no difference in effectiveness between Guided Inquiry and Problem Based Learning learning models to improve learning competency aspects of knowledge tcount of 0.2764> t table 1.6725.